Identification of Conserved and Novel MicroRNAs in Blueberry - Yue, Junyang; Lu, Xiaohui; Zhang, Huan; Ge, Jiao; Gao, Xueling; Liu, Yongsheng (Frontiers in Plant Science, 2017)
MicroRNAs (miRNAs) are a class of small endogenous RNAs that play important regulatory roles in cells by negatively affecting gene expression at both transcriptional and post-transcriptional levels. There have been extensive studies aiming to identify miRNAs and to elucidate their functions in various plant species. In the present study, we employed the high-throughput sequencing technology to profile miRNAs in blueberry fruits. A total of 9,992,446 small RNA tags with sizes ranged from 18 to 30 nt were obtained, indicating that blueberry fruits have a large and diverse small RNA population. Bioinformatic analysis identified 412 conserved miRNAs belonging to 29 families, and 35 predicted novel miRNAs that are likely to be unique to blueberries. Among them, expression profiles of five conserved miRNAs were validated by stem loop qRT-PCR. Furthermore, the potential target genes of conserved and novel miRNAs were predicted and subjected to Gene Ontology (GO) annotation. Enrichment analysis of the GO-represented biological processes and molecular functions revealed that these target genes were potentially involved in a wide range of metabolic pathways and developmental processes. Particularly, anthocyanin biosynthesis has been predicted to be directly or indirectly regulated by diverse miRNA families. This study is the first report on genome-wide miRNA profile analysis in blueberry and it provides a useful resource for further elucidation of the functional roles of miRNAs during fruit development and ripening.